Endoscopic Submucosal Dissection for Large Colorectal Tumor in a Japanese General Hospital - Ohata, Ken (Hindawi Publishing Corporation, 2013)
Background and Aims. Endoscopic submucosal dissection (ESD) is not widely used in large colorectal lesions because of technical difficulty and possible complications. We aimed to examine the efficacy and safety of ESD for large colorectal neoplasms. Patients and Methods. During the past 5 years, 608 cases of colorectal neoplasm (≧20 mm) were treated by ESD. They were divided into Group A (20–49 mm, 511 cases) and Group B (≧50 mm, 97 cases). Results. The average age, lesion size, and procedure time were 67.4 years, 30.0 mm, and 60.0 min in Group A, and they were 67.1 years, 64.2 mm, and 119.6 min in Group B. En bloc resection rates were 99.2% and 99.0% (P = 0.80), and complication rates were 4.1% and 9.9% (P = 0.03). Complications in Group A consisted of perforation (2.7%), bleeding (1.2%), and ischemic colitis (0.2%). Those in Group B were perforation (8.2%) and bleeding (1.0%). Two cases in Group A and none in Group B required emergency surgery for perforation. Conclusions. There was no difference in efficacy between Groups A and B. Complications were more frequent in Group B, but all perforations in Group B were successfully managed conservatively. ESD can be effective and safe for large colorectal tumors.